Direct, Inverse Theorems of Approximation by Linear Combinations of Weighted Baskakov–Durrmeyer Operators in Orlicz Spaces (Analysis in Theory and Applications, 2024)
In the paper, the authors introduce the Orlicz space corresponding to theYoung function and, by virtue of the equivalent theorem between the modified $K$-functional and modulus of smoothness, establish the direct, inverse, and equivalenttheorems for the linear combinations of Jacobi weighted Baskakov–Durrmeyer operators in the Orlicz spaces.